Application of Virtual Reality, Augmented Reality, and Mixed Reality in Endourology and Urolithiasis: An Update by YAU Endourology and Urolithiasis Working Group - Hameed, B. M. Zeeshan; Somani, Shraddha; Keller, Etienne Xavier; Balamanigandan, R.; Mahapatra, Satyasundara; Pietropaolo, Amelia; Tonyali, Şenol; Juliebø-Jones, Patrick; Naik, Nithesh; Mishra, Dilip; Kumar, Sarvesh; Chlosta, Piotr; et al. (Frontiers in Surgery, 2022)
The integration of virtual reality (VR), augmented reality (AR) and mixed reality (MR) in urological practices and medical education has led to modern training systems that are cost-effective and with an increased expectation towards surgical performance and outcomes. VR aids the user in interacting with the virtual environment realistically by providing a three-dimensional (3D) view of the structures inside the body with high-level precision. AR enhances the real environment around users by integrating experience with virtual information over physical models and objects, which in turn has improved understanding of physiological mechanisms and anatomical structures. MR is an immersive technology that provides virtual content to interact with real elements. The field of urolithiasis has adapted the technological advancements, newer instruments, and methods to perform endourologic treatment procedures. This mini-review discusses the applications of Virtual Reality, Augmented Reality, and Mixed Reality in endourology and urolithiasis.